Whole-cell vaccine candidates induce a protective response against virulent Acinetobacter baumannii - Dollery, Stephen J.; Zurawski, Daniel V.; Bushnell, Ruth V.; Tobin, John K.; Wiggins, Taralyn J.; MacLeod, David A.; Tasker, Naomi J. P. E. R.; Alamneh, Yonas A.; Abu-Taleb, Rania; Czintos, Christine M.; Su, Wanwen; Escatte, Mariel G.; et al. (Frontiers in Immunology, 2022)
Acinetobacter baumannii causes multi-system diseases in both nosocomial settings and a pre-disposed general population. The bacterium is not only desiccation-resistant but also notoriously resistant to multiple antibiotics and drugs of last resort including carbapenem, colistin, and sulbactam. The World Health Organization has categorized carbapenem-resistant A. baumannii at the top of its critical pathogen list in a bid to direct urgent countermeasure development. Several early-stage vaccines have shown a range of efficacies in healthy mice, but no vaccine candidates have advanced into clinical trials. Herein, we report our findings that both an ionizing γ-radiation-inactivated and a non-ionizing ultraviolet C-inactivated whole-cell vaccine candidate protects neutropenic mice from pulmonary challenge with virulent AB5075, a particularly pathogenic isolate. In addition, we demonstrate that a humoral response is sufficient for this protection via the passive immunization of neutropenic mice.